(untitled) (Research, Society and Development, 2021)
The concern and care with the physical appearance has been increasing more and more, thus expanding the search for aesthetic techniques used to treat skin and body imperfections. Flaccidity is a "sequel" caused by several episodes that have occurred over the years, such as lack of physical activity, excessive weight loss, aging, among others. The main objective of this article is to analyze and expose the various studies and research on the effects of radiofrequency in patients with tissue flaccidity. It is a narrative literature review, with the aim of allowing the abstract to increase and reach information relatively on a delimited topic in a short period of time. The research was carried out in the main databases in the health area: Scientific Electronic Library Online (SCIELO), PUBMED, LILACS (Latin American and Caribbean Literature in Health Sciences) and Google Scholar with the following themes: Radiofrequency, Tissue Flaccidity and Physiotherapy. Radiofrequency has stood out both to promote physiological and aesthetic changes. Through the therapy used for this treatment of tissue flaccidity, it found firmness in the skin tissue through the effect resulting from the deep heat, which is generated as a result of the radiofrequency, propagating through the internal to the external environment and thus causing the degradation of the aged collagen. From this research, it was observed that Radiofrequency has positive results in the treatment of supporting the skin, stimulating collagen fibers and thus reducing sagging skin.